Body sway and sensory motor coupling adaptation in children: Effects of distance manipulation - Godoi, Daniela [UNESP]; Barela, Jose A. [UNESP] (Wiley-Blackwell, 2008)
The purpose of this investigation was to examine coupling between visual information and body sway in children and young adults at various distances from a moving room front wall. Sixty children (from 4 to 14 years old) and 10 young adults stood upright inside a moving room that was oscillated at .2 and .5 Hz, at distances of .25, .5, 1, and 1.5 m from a front wall. Visual information induced body sway in all participants in all conditions. Young children swayed more than older participants, whether the moving room was oscillated or not. Coupling between visual information and body sway became stronger and the room movement influence became weaker with age. Up to the age of 10, coupling strength between visual information and body sway and the room movement influence were distance dependent. Postural control development appears to be dependent on how children reweight the contribution of varying sensory cues available in environment in order to control body sway. (C) 2007 Wiley Periodicals, Inc.
Keywords: posture; development; vision; sensorimotor; moving room